2008
DOI: 10.1186/1752-0509-2-52
|View full text |Cite
|
Sign up to set email alerts
|

A computational analysis of protein-protein interaction networks in neurodegenerative diseases

Abstract: Background: Recent developments have meant that network theory is making an important contribution to the topological study of biological networks, such as protein-protein interaction (PPI) networks. The identification of differentially expressed genes in DNA array experiments is a source of information regarding the molecular pathways involved in disease. Thus, considering PPI analysis and gene expression studies together may provide a better understanding of multifactorial neurodegenerative diseases such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 37 publications
3
64
0
3
Order By: Relevance
“…Recently, a number of approaches analyzed bottlenecks in human protein-protein interaction networks. These studies have identified genes involved in neurodegenerative diseases (Goni et al, 2008), and characterized properties of successful drug targets (Yao and Rzhetsky, 2008) and targets of different pathogens (Dyer et al, 2008). Bottleneck nodes in other types of networks, for example those derived from mining literature, have also been used to identify disease-associated genes (Ozgur et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of approaches analyzed bottlenecks in human protein-protein interaction networks. These studies have identified genes involved in neurodegenerative diseases (Goni et al, 2008), and characterized properties of successful drug targets (Yao and Rzhetsky, 2008) and targets of different pathogens (Dyer et al, 2008). Bottleneck nodes in other types of networks, for example those derived from mining literature, have also been used to identify disease-associated genes (Ozgur et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the constructed DEN revealed that six genes (APP, UBC, CAND1, RPA, YWHAG, and NEDD8) were hub nodes and none was a DEG. DEGs, showing significantly different expression profiles in the case and control groups, are usually found using traditional statistical techniques, such as the t-test or fold change (Goñi et al, 2008;Ray and Zhang, 2010). Although DEGs are regarded as candidates for a role in pathogenesis, they are generally selected out separately, while co-expression of genes is ignored (Kostka and Spang, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Systems biology has applications in various areas related to medicine, including biomarker discovery, improvement of drug target identification and prognosis assessment [101,102]. For example, using network analysis, one of the most pursued approaches in systems biology, we were able to identify Jagged-1/Notch as a candidate therapeutic target for MS [103].…”
Section: Systems Biology Approach For the Development Of Personalizedmentioning
confidence: 98%